157 Efficacy of adjunctive cenobamate: post-hoc analysis in patients grouped by concomitant anti-epileptic drug type. Issue 6 (27th May 2022) - Brandt, Christian; Serratosa, Jose; Sanchez-Alvarez, Juan; Alvarez-Baron, Elena; Finlan, Lee; Milanov, Ivan; Steinhoff, Bernhard J
Abstract : Purpose: There has been little success with polytherapy for patients with drug-resistant epilepsy. The need for optimizing AED combinations is high. Cenobamate is a novel AED with a unique, dual, complementary mechanism of action (MoA) combining GABA-A positive allosteric modulation (via a binding site different from benzodiazepines) together with broad spectrum sodium channel blockage. Here we assessed the efficacy of cenobamate when combined with AEDs grouped by MoA. Methods: A post-hoc exploratory analysis of the study C017, in adult epilepsy patients with uncontrolled focal onset seizures who had ≥4 seizures/month despite treatment with stable doses of 1–3 AEDs. Results: In the maintenance phase, 183/397 (46%) patients were receiving at least one GABA modulator (felbamate, valproate, topiramate, tiagabine, vigabatrin) and 329/397 (82%) a sodium channel blockers (carbamazepine, oxcarbazepine, lamotrigine, lacosamide, eslicarbazepine). Added onto GABA modu- lators, cenobamate 100/200/400mg achieved seizure freedom rates (SFR) of 7.3%/15.6%/30.6% vs 2.1% for placebo; when added onto sodium channel blockers, cenobamate 100/200/400mg/day showed SFR of 2.3%/9.3%/17.5% vs 1.2% for placebo. Both results were statistically significant for 200 and 400mg. A consistent SFR with cenobamate for a subset of patients receiving background levetiracetam (11% 200mg and 25% 400 mg vs 2.5% placebo) as well as those with background benzodiazepines (20% 400 mg vs 0% placebo) occurred. Conclusions: Adjunctive cenobamate achieved significant dose-dependent SFR when combined with AEDs across multiple MoAs in patients with uncontrolled FOS. lee.finlan@arvelletx.com